Noise and Lighting Measurement and Analysis for Industrial Work Area X, Jakarta City - Disfiatri Kusumaningtyas; Betanti Ridhosari; Ariyanti Sarwono; I Wayan Koko Suryawan (Journal of Sustainable Infrastructure, 2023)
Noise and lighting are some of the factors that affect occupational health in the industry. The manufacturing industry needs to look at the quality of noise and lighting to determine efforts to prevent health risks. This study aims to analyze industry noise and lighting values ​​and compare them with the established standards. Measurements in this study were carried out using interviews with workers to determine the dominant location providing noise and lighting values. The average noise in the work area in the study industry shows a value that exceeds the standard. The noise value in the work area shows a value of 86.56 - 89.79 dB(A), while in the rest, it can reach a value that meets the quality standard, which is 74.65 dB(A). The lighting at one work station shows a value that does not meet the standard, namely 168.7 LUX, while in other work areas it meets the value of 201.3 – 203 LUX.